2016
DOI: 10.1242/dev.133363
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 signaling is essential for nerve-dependent axolotl limb regeneration

Abstract: The Mexican axolotl (Ambystoma mexicanum) is capable of fully regenerating amputated limbs, but denervation of the limb inhibits the formation of the post-injury proliferative mass called the blastema. The molecular basis behind this phenomenon remains poorly understood, but previous studies have suggested that nerves support regeneration via the secretion of essential growthpromoting factors. An essential nerve-derived factor must be found in the blastema, capable of rescuing regeneration in denervated limbs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 48 publications
1
94
0
Order By: Relevance
“…A more detailed study of neuregulin 1 (NRG1) in regenerating axolotl limbs (Farkas, Freitas, Bryant, Whited, & Monaghan, 2016) showed that transcripts of nrg1 and its receptors erbb2 and erbb3 are expressed by the basal cells of the AEC and by 56% of the blastema mesenchyme cells. Antibody staining revealed expression of NRG1 and ErbB2 in dorsal root ganglia and peripheral limb nerves.…”
Section: Blastema Growthmentioning
confidence: 99%
“…A more detailed study of neuregulin 1 (NRG1) in regenerating axolotl limbs (Farkas, Freitas, Bryant, Whited, & Monaghan, 2016) showed that transcripts of nrg1 and its receptors erbb2 and erbb3 are expressed by the basal cells of the AEC and by 56% of the blastema mesenchyme cells. Antibody staining revealed expression of NRG1 and ErbB2 in dorsal root ganglia and peripheral limb nerves.…”
Section: Blastema Growthmentioning
confidence: 99%
“…[7][8][9][10] Substitute molecules for nerve functions in blastema induction have been tested for, and some candidate genes have been described. 6,[11][12][13][14][15] Recently, a brand-new experimental system called the accessory limb model (ALM) proposed the nerve molecules that can induce regeneration in multiple organs and species. 13,14,[16][17][18][19][20] The ALM is a better experimental design for the investigation of nerve functions in limb regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neurons or macrophages can act as sources of GFs at the wound site (Brockes & Kintner, ; Lu et al, ; L. Wang, Marchionni, & Tassava, ). In many of these instances (mammalian bone and cartilage (Kempen et al, ), blood vessels (Gasparini, Burighel, Manni, & Zaniolo, ; Koch & Claesson‐Welsh, ), heart (Uva et al, ; Wadugu & Kuhn, ), and liver (Mao, Glorioso, & Scott, ), amphibian lens (Henry, Thomas, Hamilton, Moore, & Perry, ) and limb (Brockes & Kintner, ; Farkas, Freitas, Bryant, Whited, & Monaghan, ; Satoh, Mitogawa, & Makanae, ), and zebrafish heart and fin regeneration (Kim et al, ; Lee, Grill, Sanchez, Murphy‐Ryan, & Poss, ; Poss et al, )), functional studies have revealed that GFs or the pathways activated by GF receptors, regulate proliferation (as either activators or inhibitors) (summarized in Figure ).…”
Section: Wound Signaling and The Regulation Of Proliferationmentioning
confidence: 99%